2019
DOI: 10.1093/jxb/erz052
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of ethanol fermentation and its regulation in land plants

Abstract: Ethanol fermentation is considered as one of the main metabolic adaptations to ensure energy production in higher plants under anaerobic conditions. Following this pathway, pyruvate is decarboxylated and reduced to ethanol with the concomitant oxidation of NADH to NAD+. Despite its acknowledgement as an essential metabolic strategy, the conservation of this pathway and its regulation throughout plant evolution have not been assessed so far. To address this question, we compared ethanol fermentation in species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 81 publications
1
49
0
Order By: Relevance
“…Although ADH is the crucial enzyme for NADH oxidation, mutations in ADH can also lead to the accumulation of acetaldehyde, which is much more toxic than ethanol 38 . The pdc1pdc2 is instead blocked at the level of pyruvate, and therefore, while the two mutants are both equally impaired in their ability to produce ethanol 39 , they differ in terms of the metabolic step blocked and the possible detrimental effects of acetaldehyde accumulating in the adh1 mutant could be revealed by differences in the phenotypes of the two mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Although ADH is the crucial enzyme for NADH oxidation, mutations in ADH can also lead to the accumulation of acetaldehyde, which is much more toxic than ethanol 38 . The pdc1pdc2 is instead blocked at the level of pyruvate, and therefore, while the two mutants are both equally impaired in their ability to produce ethanol 39 , they differ in terms of the metabolic step blocked and the possible detrimental effects of acetaldehyde accumulating in the adh1 mutant could be revealed by differences in the phenotypes of the two mutants.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently unclear which hypoxia-responsive genes actually contribute to enhanced hypoxia tolerance. For instance, several studies suggest transcriptional SUS1 or ADH1 induction may not be required for anaerobic fermentation, maintenance of glycolysis and subsequent hypoxia tolerance in potato tubers and Arabidopsis, respectively [40,52]. Previous research showed that protein levels of ADH1 in tomato roots increased only 1.7-fold after 24 h of waterlogging, whereas PDC1 levels were even down-regulated [53].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a recent study in Arabidopsis revealed that ADH activity was up-regulated in a PDC-inactivated mutant (Bui et al, 2019). Given that the authors observed that gene expression levels in mutant and wild-type plants were essentially the same, they concluded that inactivation of PDC activity promotes the accumulation of ADH protein (Bui et al, 2019). We suspect that similar, as yet undetermined, mechanisms may suppress gene expression of ADH in rice during germination.…”
Section: Discussionmentioning
confidence: 91%
“…At present, however, we are unable to explain why SL2111 shows lower ADH1 expression, even though this line was characterized by a longer coleoptile under anaerobic conditions. In this regard, a recent study in Arabidopsis revealed that ADH activity was up-regulated in a PDC-inactivated mutant (Bui et al, 2019). Given that the authors observed that gene expression levels in mutant and wild-type plants were essentially the same, they concluded that inactivation of PDC activity promotes the accumulation of ADH protein (Bui et al, 2019).…”
Section: Discussionmentioning
confidence: 99%